Public Management on the Ground: Clustering Managers Based on Their Behavior. Issue 2 (15th March 2019) - Pedersen, Mogens Jin; Favero, Nathan; Nielsen, Vibeke Lehmann; Meier, Kenneth J.
ABSTRACT: Public management research has identified a dizzying array of management variables that affect organizational performance. While scholars have learned much by analyzing one or a few specific behavioral dimensions of public management at a time, we argue for the value of a more holistic and inductive approach that uses data on several aspects of public management for identifying manager types. Such an approach accounts for both the cognitive processes of people affected by management and the reality that managers' individual behavioral decisions are interrelated. We examine the overlap of 21 aspects of public school management behavior using cluster analysis. We identify four different manager types ("firefighters, " "laissez-faire managers, " "administrators, " and "proactive floor managers"), each reflecting a distinct constellation of managerial behaviors. The manager types we call "administrators" and "proactive floor managers" are associated with relatively better outcomes, while "firefighters" are associated with relatively worse outcomes.